2001
DOI: 10.1097/00005537-200105000-00023
|View full text |Cite
|
Sign up to set email alerts
|

A Morphological Study of Age Changes in Adult Human Auricular Cartilage With Special Emphasis on Elastic Fibers

Abstract: Structural changes of auricular cartilage associated with morphological age changes of elastic fibers may be one of the causes of expansion of the auricle after reaching adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
83
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 18 publications
14
83
1
2
Order By: Relevance
“…Sharma et al found that the linear ear dimensions increased with advancing age [11]. To add to it, the auricular growth ceases at 13 years for males and at 12 years for females [12].…”
Section: Resultsmentioning
confidence: 99%
“…Sharma et al found that the linear ear dimensions increased with advancing age [11]. To add to it, the auricular growth ceases at 13 years for males and at 12 years for females [12].…”
Section: Resultsmentioning
confidence: 99%
“…We know that the size of human auricle continues to increase even after completion of development and reaching adulthood 14,15 . Length and width increments of the auricle during various stages of life and differences between the sexes were estimated in several studies 9,10,15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Length and width increments of the auricle during various stages of life and differences between the sexes were estimated in several studies 9,10,15,16 . The explanations for this phe- nomenon were diverse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the ear gives information about age and sex, which is clear. But, still has difficulties in characterizing it [2][3][4][5][6]. The size of the human auricle increases between 0 and 18 ages [7], and its size continues to increase even after the body development finishes [5][6].…”
Section: Sonuçmentioning
confidence: 99%